2014
DOI: 10.1021/jp502476x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Functional Characterization of the Collagen–Polyvinylpyrrolidone Copolymer

Abstract: Collagen-polyvinylpyrrolidone (C-PVP) is a copolymer that is generated from the γ irradiation of a mixture of type I collagen and low-molecular-weight PVP. It is characterized by immunomodulatory, fibrolytic, and antifibrotic properties. Here, we used various physicochemical and biological strategies to characterize the structure, biochemical susceptibility, as well as its effects on metabolic activity in fibroblasts. C-PVP contained 16 times more PVP than collagen, but only 55.8% of PVP was bonded. Neverthele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[29][30][31][32][33][34] The interaction between collagen and PVP in blends has been studied by Sionkowska 35 and further investigated the effects of UV-irradiation on collagen-PVP composition and surface properties. 36,37 -radiation synthesis of various types of collagen-PVP hydrogels is described by Leyva-Gomez et al, Gonzales-Torres et al, and Demeter et al [38][39][40] The collagen/PVP/PEG hydrogel prepared by -radiation, showed the improvement in fibroblasts viability when the PEG/PVP concentrations were lower. 39 In our previous study, we have investigated the network structure of collagen-PVP hydrogels produced by -irradiation and we have determined that hydrogels with an elastic character (elastic modulus (G') larger than viscous modulus (G'')) were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] The interaction between collagen and PVP in blends has been studied by Sionkowska 35 and further investigated the effects of UV-irradiation on collagen-PVP composition and surface properties. 36,37 -radiation synthesis of various types of collagen-PVP hydrogels is described by Leyva-Gomez et al, Gonzales-Torres et al, and Demeter et al [38][39][40] The collagen/PVP/PEG hydrogel prepared by -radiation, showed the improvement in fibroblasts viability when the PEG/PVP concentrations were lower. 39 In our previous study, we have investigated the network structure of collagen-PVP hydrogels produced by -irradiation and we have determined that hydrogels with an elastic character (elastic modulus (G') larger than viscous modulus (G'')) were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the viscosity profiles, the rheology analysis was performed in a viscometer (Brookfield CAP 2000 viscometer, USA), using the No.1 needle, with a constant temperature of 37 °C and controlled humidity. The shear rate experiment was performed from 1,600-8,000 s -1 and vice versa at intervals of 1,600 s -1 , the viscosity records were made after rotating for 20 s at each shear rate (16). Also, experiments at the constant shear rate were carried out at 2,000 s -1 during 1,800 s. The viscosity record was made every 120 s. Each sample was analyzed in triplicate using 250 µL of sample per analysis.…”
Section: Rheologymentioning
confidence: 99%
“…In general, IR is used when the sample is not extremely complicated, and signals in the spectra can be assigned to specific interactions in the gel as a chemical modifier as a cross-linker for instance [45,46]. In such a way, another classical technique that determines chemical interactions among distinct parts of a composite, as 1 H-NMR can be used also in ECMs [47].…”
Section: Spectroscopy Techniquesmentioning
confidence: 99%
“…It has been also suggested that collagen denaturation can be determined by viscosimetric measurements [66]. Those experiments become important in the case of development of injectable systems because parameters as viscosity [47,67] and compressibility [52] are important during extrusion. Rheological methods described previously are also convenient to measure the formation of the gel in time: storage (G´) (colloquially speaking, how much the viscoelastic material looks like a solid) and loss modulus (G´´) (how much the viscoelastic material looks like a liquid) can be determined in an oscillatory rheological measurement to get the gel formation point: where the storage modulus becomes higher than the loss modulus (G´ > G´´) [68].…”
Section: Mechanical Testsmentioning
confidence: 99%